The Influence of Social Media Sites on Consumer Buying Behavior in Shoprite Nigeria Limited - Mulikat Abdulraheem; Ebun Omoniyi Imouokhome (Binus Business Review, 2021)
Business organizations are continually searching for new ways to reach out to their consumers. Before, television, radio, and print are usually used by businesses to advertise their products. The coming of social media has shifted the way organizations interacting with their targeted audience. It has made social media an important tool for maintaining and creating a competitive advantage. Businesses today embrace the use of social media without paying adequate attention to silent issues concerning the usage of sites that can influence consumer buying behavior. The research aimed to examine the influence of social media sites on consumer buying behavior in Shoprite Nigeria Limited. The examined social media sites included Twitter, Facebook, Google+, blogs, and YouTube. The research was a descriptive design. The population was made up of consumers of Shoprite Nigeria Limited in Ibadan and Lagos. The sample size was 384 using Cochran's 1977 sample size formula for the infinite population. However, only 321 respondents filled and returned the questionnaires. A structured questionnaire was designed using a five-point Likert scale of agreement. Then, a hypothesis was tested using multiple regression analysis. The result shows that the null hypothesis is rejected. It implies that social media sites influence consumer buying behavior in Shoprite Nigeria Limited. It concludes that social media sites are important tools that can influence consumer buying behavior. It is recommended that the organization should invest more in social media sites to get in touch with their targeted audience.